2011
DOI: 10.1007/s00420-011-0712-x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and effort–reward imbalance improvement for teachers by a manual-based group program

Abstract: Teachers' occupational stress level may be decreased by taking part in a short manual-based psychological group intervention that focuses on more effective handling of interpersonal problems in school. Therefore, teachers should receive support and guidance in developing the appropriate skills necessary to cope with stress appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 33 publications
2
47
1
Order By: Relevance
“…Mino et al [4] conducted a 3-month, randomized controlled trial in Japan with significant effects on depression. Two further randomized controlled trials in Germany found effects of SMI on work stress and burnout over a period of 6 months [5] or 1 year [6]. Importantly, our study, using psychodynamic principles together with cognitive-behavioral techniques, documented a significant improvement in psychosocial stress and mental health at work, thus extending the research findings of long-term effectiveness of psychotherapy on common mental disorders from the clinical to the occupational setting [2].…”
Section: Tablesupporting
confidence: 53%
See 1 more Smart Citation
“…Mino et al [4] conducted a 3-month, randomized controlled trial in Japan with significant effects on depression. Two further randomized controlled trials in Germany found effects of SMI on work stress and burnout over a period of 6 months [5] or 1 year [6]. Importantly, our study, using psychodynamic principles together with cognitive-behavioral techniques, documented a significant improvement in psychosocial stress and mental health at work, thus extending the research findings of long-term effectiveness of psychotherapy on common mental disorders from the clinical to the occupational setting [2].…”
Section: Tablesupporting
confidence: 53%
“…SMI in the workplace could best be based on theoretical models that include a personal as well as a situational component of intervention. The Effort-Reward Imbalance (ERI) model [3] is one such model that has been used to guide intervention studies in recent years [4,5,6,7]. The ERI model includes the situation-specific component, which emphasizes the harmful effects of failed reciprocity between efforts spent at work and rewards received in turn (high effort/low reward), and the person-specific component termed ‘overcommitment', which is a distinct pattern of coping with demanding situations characterized by an inability to withdraw from work obligations.…”
Section: Tablementioning
confidence: 99%
“…Most of the interventions to prevent work-related stress in education aim to increase the resources of the individual to deal with the demands of the job [510]. However, these interventions were only partially effective in influencing (dimensions of) burnout [57, 9, 10] and well-being [10]. Explanations for this lack of effectiveness could be the level the intervention is aimed at (ie secondary or tertiary prevention), whereas it is proposed that problems should also be addressed at the source (primary prevention) and organizational level to sustainably decrease work-related stress.…”
Section: Introductionmentioning
confidence: 99%
“…The same holds true for stress management interventions in the educational sector. Until now stress management interventions in education have been ‘secondary preventive’ mostly and targeted at the individual level [24-28]. These interventions [24-28] all aimed to enhance the individual capacity of (trainee) teachers or teaching assistants to cope with stressors in the workplace, for example via mindfulness-based stress reduction or workshops on stress management skills.…”
Section: Introductionmentioning
confidence: 99%
“…Until now stress management interventions in education have been ‘secondary preventive’ mostly and targeted at the individual level [24-28]. These interventions [24-28] all aimed to enhance the individual capacity of (trainee) teachers or teaching assistants to cope with stressors in the workplace, for example via mindfulness-based stress reduction or workshops on stress management skills. However, these interventions were only partly effective in influencing (dimensions of) burnout [24-28] and well-being [28].…”
Section: Introductionmentioning
confidence: 99%